Endoscopic submucosal dissection of malignant non-pedunculated colorectal lesions - Rönnow, Carl-Fredrik; Elebro, Jacob; Toth, Ervin; Thorlacius, Henrik (Endoscopy International Open, 2018)
Background and study aims Endoscopic submucosal dissection (ESD) is an established method for en bloc resection of large non-pedunculated colorectal lesions in Asia but dissemination of ESD in Western countries is limited. The aim of this study was to evaluate the role of ESD in the management of malignant non-pedunculated colorectal lesions in a European center.Patients and methods Among 255 patients undergoing colorectal ESD between 2014 and 2016, 29 cases were identified as submucosal invasive cancers and included in this study. The main outcomes were en bloc, R0 and curative resection as well as procedural time, complications and recurrence.Results Median tumor size was 40 mm (range 20 – 70 mm). Thirteen cancers were located in the colon and 16 were located in the rectum. Procedural time was 89 minutes (range 18 – 594 minutes). Complete resection was achieved in 28 cases, en bloc and R0 resection rates were 83 % and 69 %, respectively. Curative resection rate was 38 %. One case had a perforation in the sigmoid colon requiring emergency surgery. No significant bleeding occurred. Six patients underwent additional surgery after ESD, one of whom had residual tumor. One recurrence was detected in 20 patients that were followed-up endoscopically, median follow-up time was 13 months (range 2 – 30 months).Conclusion ESD seems to be a safe and effective method for treating non-pedunculated malignant colorectal lesions after careful patient selection and proper endoscopic training.